Long noncoding RNA regulatory factor X3- antisense RNA 1 promotes non-small cell lung cancer via the microRNA-577/signal transducer and activator of transcription 3 axis. Issue 4 (1st April 2022) - Hu, Yanjing; Zhao, Zhi; Jin, Gang; Guo, Junhao; Nan, Fangyuan; Hu, Xin; Hu, Yunsheng; Han, Qun
ABSTRACT: Lung cancer is the most frequent malignancy, and non-small cell lung cancer (NSCLC) is its most common pathological type. Molecular targeted therapy has been testified to be effective in intervening in the occurrence and development of malignancies. This study investigates the effect of lncRNA Regulatory Factor X3- antisense RNA 1 (RFX3-AS1) in NSCLC progression. The RFX3-AS1 profile in NSCLC tissues and cells was measured by quantitative reverse transcription PCR (qRT-PCR). The RFX3-AS1 overexpression model was constructed. The cell counting kit-8 (CCK-8) experiment and cell colony formation assay were adopted to test cell viability. The cell apoptosis was determined by flow cytometry (FCM). Cell migration and invasion were monitored by the Transwell assay, and Western blot was implemented to verify the protein profiles of signal transducer and activator of transcription 3 (STAT3), E-cadherin, Vimentin and N-cadherin. In vivo, we validated the impact of RFX3-AS1 overexpression on the NSCLC xenograft mouse model. The targeting relationships between RFX3-AS1 and miR-577, miR-577 and STAT3 were confirmed by the dual-luciferase reporter assay. The results manifested that overexpressing RFX3-AS1 markedly facilitated NSCLC cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT), and suppressed cell apoptosis. In contrast, miR-577, which was a downstream target of RFX3-AS1, dramatically impeded the malignant biological behaviors of NSCLC cells. STAT3 was a direct target of miR-577, and it was negatively regulated by the latter. STAT3 activation reversed miR-577-mediated anti-tumor roles. In brief, RFX3-AS1 aggravated NSCLC progression by regulating the miR-577/STAT3 axis. Graphical Abstract: uf0001